Determinación del costo de producción estándar y su influencia en la rentabilidad de la empresa Interfilk S.A ubicada en lomas de sargentillo provincia del guayas en el periodo 2022 - Chiluisa Menéndez, Nathaly Valentina (2023)
The present work of curricular integration entitled "Determination of the standard production cost and its influence on the profitability of the company INTERFILK S.A. located in Lomas de Sargentillo province of Guayas in the period 2022", aims to demonstrate the production process carried out by the company according to a system of historical costs and the profitability that this generates for the company. Assigning a new production process of goods, the correct allocation of sales prices and the feasibility of decision making for Interfilk S.A. is one of the main objectives of the study. An adequate product manufacturing follow-up, according to the proper production orders, will help to reduce unnecessary production costs for the company. For this reason, it is suggested the correct application of a standard cost system that is in charge of evaluating the productive efficiency of Interfilk S.A., facilitating the control of its costs and prevailing the estimated profitability within the determined periods. Finally, the methodology used in the research will present a mixed approach, related to its dependent and independent variable, with the application of the appropriate data collection instruments that will facilitate the obtaining of the expected results.Finally, in relation to the results obtained based on the correlational system analysis technique and the data measurement instruments, the necessary answers are obtained to clear the hypothesis of the study, giving as a result that the determination of the standard costs would be more favorable for the company, which would be reflected in its profitability.